Low influenza vaccine effectiveness and the effect of previous vaccination in preventing admission with A(H1N1)pdm09 or B/Victoria-Lineage in patients 60 years old or older during the 2015/2016 influenza season. Issue 52 (19th December 2017) - Puig-Barberà, Joan; Guglieri-López, Beatriz; Tortajada-Girbés, Miguel; López-Labrador, F. Xavier; Carballido-Fernández, Mario; Mollar-Maseres, Joan; Schwarz-Chavarri, Germán; Baselga-Moreno, Víctor; Mira-Iglesias, Ainara; Díez-Domingo, Javier; ,
Abstract: Background: The 2015/2016 influenza season was characterized in Europe by the circulation of A(H1N1)pdm09 clade 6B.1 and B/Victoria-lineage influenza viruses. The components of the vaccines used in the current and past two seasons in the Valencia region were similar but not well matched to the 2015/2016 dominant influenza-circulating strains. We estimate influenza vaccine effectiveness (IVE) and interference of previous vaccination in preventing admission with A(H1N1)pdm09 or B/Victoria-lineage in this particular season. Methods: The Valencia Hospital Network for the Study of Influenza runs an active surveillance hospital-based study to collect clinical and virological data from consecutive admissions possibly related to influenza. Combined nasopharyngeal and pharyngeal swabs are analyzed by reverse transcription polymerase chain reaction, and the hemagglutinin is sequenced in a sample of positive influenza specimens. Vaccination is ascertained consulting a population vaccine information system. We estimate IVE using a test-negative approach. Results: During the 2015–2016 season, we recruited 1049 eligible admissions of patients 60 years or older, and 187 tested positive for influenza. The adjusted IVE in preventing admission with A(H1N1)pdm09 was 20.2%; 95% confidence interval (CI) −21.3–47.5% and −33.2%; 95% CI, −140.1–26.1% in preventing admission with B/Victoria-lineage. The majority of A(H1N1)pdm09 sequenced viruses belonged to the emerging 6B.1 subclade, defined by S162N and I216T mutations in the hemagglutinin protein. When we restricted our analysis to those not vaccinated in the previous year, unadjusted IVE was 84.9% (95% CI 9.9–100.0) overall, 77.9% (−32.7–100.0%) in preventing A(H1N1)pdm09 and 48.8% (−219.5–100.0%) in preventing B/Yamagata-lineage admission. Conclusions: Our findings indicate that IVE was low in preventing A(H1N1)pdm09 and strongly correlated with vaccination in the previous season. No effect in preventing admission with B/Victoria-lineage was observed. For the 2015/2016 season, IVE was low due to a mismatch and lack of concordance between the circulating and vaccine viruses.